Robinson Crusoe - Defoe, Daniel, 1661?-1731.; Bown, Derick (Milwaukee : Raintree Childrens Books, 1978)
During a voyage in the 1600's an Englishman becomes the sole survivor of a shipwreck and lives for almost thirty years on a desert island before being rescued.
Cataloging based on CIP information.
Keywords: Shipweck survival -- Juvenile fiction; Crusoe, Robinson (Fictitious character) -- Juvenile fiction; Shipwrecks -- Fiction; Survival -- Fiction